Masculine Expansions of Othermothering in Toni Morrison’s A Mercy, Jazz, and Beloved - Mercer, Naomi (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
Othermothering in African American communities began as a system of childcare but has evolved into the care of individuals in need. Toni Morrison’s work presents myriad examples of othermothering performed by black women. Perhaps more intriguing are the sites where othermothering as a system of care work in Morrison’s novels serves to subvert gender and race norms. Some critics argue that Morrison’s depictions of female-centric othermothering allow black men to shirk parental and communal responsibilities and assign less responsibility to black men for carrying on the traditions and culture of the African American community than black women. However, this article examines how male othermothering in Beloved, Jazz, and A Mercy expands the master narrative of the ideal (black or white) mother by refuting gender roles and the naturalization of women as better suited to care giving. Morrison’s depictions of masculine othermothering as a valuable source of care challenge the ideology of the nuclear family for its primacy as a family model.